Fuzzy logic to evaluate significant factors affecting students’ academic performance through Online Distance Learning / Mohd Fazril Izhar Mohd Idris, Khairu Azlan Abd Aziz & Muhammad Haiman Aminuddin - Mohd Idris, Mohd Fazril Izhar; Abd Aziz, Khairu Azlan; Aminuddin, Muhammad Haiman (UiTM Cawangan Perlis, 2022)
Online distance learning is becoming more and more popular and more preferred among students. In order to develop efficient strategies and solutions for introducing online distance learning, higher education institutions should be aware of the needs and expectations of their students. In the current study, students from University of Technology MARA will investigate which factors that affect the execution of online distance learning for academic performance. Time management, learning environment, internet connection, and learning method are among the factors under consideration, as determined by a literature review. The information was gathered through an online survey of 331 students whose academic performance is affected by online distance learning. An expert system based on fuzzy logic has been developed to determine which factors have the greatest influence on students' academic performance in online distance learning. According to the results obtained using the MATLAB software, one of the most important factors influencing students' academic performance in online distance learning is time management. The findings of this study will help students to improve time management in order to improve students’ academic performance.